Weaving Indigenous and Western knowledge systems across a continuum of knowledge and decision-making spaces - Natalie C Ban; Hannah V Watkins; Robyn E Forrest; Alejandro Frid; Carrie A Holt; Sierra J Hall; Christina N Service; Luisa Ramirez; Daniel L Curtis; Kyle L Wilson; Lawrence Ignace; Andrea J Reid; et al. (Current Opinion in Environmental Sustainability, 2026)

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

SNOOPI: Demonstrating Earth remote sensing using P-band signals of opportunity (SoOp) on a CubeSat - James L. Garrison; Manuel A. Vega; Rashmi Shah; Justin R. Mansell; Benjamin Nold; Juan Raymond; Roger Banting; Rajat Bindlish; Kameron Larsen; Seho Kim; Weihang Li; Mehmet Kurum; et al. (Advances in Space Research, 2024)

How to estimate age of old bottlenose dolphins (Tursiops truncatus); by tooth or pectoral flipper? - Ashley Barratclough; Wayne E. McFee; Megan Stolen; Aleta A. Hohn; Gretchen N. Lovewell; Forrest M. Gomez; Cynthia R. Smith; Daniel Garcia-Parraga; Randall S. Wells; Celeste Parry; Risa Daniels; Sam H. Ridgway; et al. (Frontiers in Marine Science, 2023)
Multiple techniques have been used for estimating age in bottlenose dolphins ( Tursiops truncatus ). The longest established technique is via counts of growth later groups (GLGs) in the longitudinal section of an extracted mandibular tooth. Previous studies to validate GLGs have primarily used younger dolphins (less than 16yrs old) due to the limited number of known age older animals. This study assessed the accuracy of age estimates for bottlenose dolphins using both GLG analysis and a newer technique, pectoral flipper radiography (PFR) for dolphins ranging from 0 to 58yrs, with a majority of samples (70%) over 16yrs. GLGs were assessed by two expert independent readers on tooth sections from 52 different dolphins (85% over 16yrs, maximum age 58yrs), and assessments of PFRs were performed by two experienced veterinarians on 37 dolphins (54% over 16yrs, maximum age 54yrs). Results demonstrated both techniques became less accurate in older dolphins, particularly those > 30yrs, with errors as large as 37yrs for GLG estimates. The root mean squared error (RMSE) for age estimation using GLGs for dolphins ≤15 years of age was 1.46yrs compared to 1.58yrs using PFRs demonstrating the accuracy of both techniques in this age bracket. For dolphins >30yrs, RMSE increased to 17yrs in GLG aging and 8.25yrs in PFR. Challenges in obtaining accurate age estimates in GLGs were primarily due to sectioning and staining difficulties in visualizing the newest GLG layers, in the very old animals. Complications in reading the layers included obtaining a good section, the presence of accessory layers, GLG compression, and tooth curvature or wear removing the neonatal line influencing aging biases. In pectoral flipper aging, the primary challenge was obtaining a true dorsoventral radiograph in a live dolphin during a health assessment, as well as the subjective assessment of scoring and reliance on degenerative changes accurately estimate age in geriatric dolphins. While access to the radiography equipment can be a limiting factor, the improved accuracy for age estimation in adult dolphins, the less invasive nature, and reduced processing time to results make pectoral radiography a preferred alternative technique for estimating age in live dolphins.

Modeling population effects of the Deepwater Horizon oil spill on a long‐lived species - Lori H. Schwacke; Tiago A. Marques; Len Thomas; Cormac G. Booth; Brian C. Balmer; Ashley Barratclough; Kathleen Colegrove; Sylvain De Guise; Lance P. Garrison; Forrest M. Gomez; Jeanine S. Morey; Keith D. Mullin; et al. (Conservation Biology, 2022)
The 2010 Deepwater Horizon (DWH) oil spill exposed common bottlenose dolphins ( Tursiops truncatus ) in Barataria Bay, Louisiana to heavy oiling that caused increased mortality and chronic disease and impaired reproduction in surviving dolphins. We conducted photographic surveys and veterinary assessments in the decade following the spill. We assigned a prognostic score (good, fair, guarded, poor, or grave) for each dolphin to provide a single integrated indicator of overall health, and we examined temporal trends in prognostic scores. We used expert elicitation to quantify the implications of trends for the proportion of the dolphins that would recover within their lifetime. We integrated expert elicitation, along with other new information, in a population dynamics model to predict the effects of observed health trends on demography. We compared the resulting population trajectory with that predicted under baseline (no spill) conditions. Disease conditions persisted and have recently worsened in dolphins that were presumably exposed to DWH oil: 78% of those assessed in 2018 had a guarded, poor, or grave prognosis. Dolphins born after the spill were in better health. We estimated that the population declined by 45% (95% CI 14–74) relative to baseline and will take 35 years (95% CI 18–67) to recover to 95% of baseline numbers. The sum of annual differences between baseline and injured population sizes (i.e., the lost cetacean years) was 30,993 (95% CI 6607–94,148). The population is currently at a minimum point in its recovery trajectory and is vulnerable to emerging threats, including planned ecosystem restoration efforts that are likely to be detrimental to the dolphins’ survival. Our modeling framework demonstrates an approach for integrating different sources and types of data, highlights the utility of expert elicitation for indeterminable input parameters, and emphasizes the importance of considering and monitoring long‐term health of long‐lived species subject to environmental disasters. Article impact statement : Oil spills can have long‐term consequences for the health of long‐lived species; thus, effective restoration and monitoring are needed.

Evolution and connectivity influence the persistence and recovery of coral reefs under climate change in the Caribbean, Southwest Pacific, and Coral Triangle - Lisa C. McManus; Daniel L. Forrest; Eden Tekwa; Daniel E. Schindler; Madhavi A. Colton; Michael M. Webster; Timothy E. Essington; Stephen R. Palumbi; Peter J. Mumby; Malin L. Pinsky (Global Change Biology, 2021)
Corals are experiencing unprecedented decline from climate change‐induced mass bleaching events. Dispersal not only contributes to coral reef persistence through demographic rescue but can also hinder or facilitate evolutionary adaptation. Locations of reefs that are likely to survive future warming therefore remain largely unknown, particularly within the context of both ecological and evolutionary processes across complex seascapes that differ in temperature range, strength of connectivity, network size, and other characteristics. Here, we used eco‐evolutionary simulations to examine coral adaptation to warming across reef networks in the Caribbean, the Southwest Pacific, and the Coral Triangle. We assessed the factors associated with coral persistence in multiple reef systems to understand which results are general and which are sensitive to particular geographic contexts. We found that evolution can be critical in preventing extinction and facilitating the long‐term recovery of coral communities in all regions. Furthermore, the strength of immigration to a reef (destination strength) and current sea surface temperature robustly predicted reef persistence across all reef networks and across temperature projections. However, we found higher initial coral cover, slower recovery, and more evolutionary lag in the Coral Triangle, which has a greater number of reefs and more larval settlement than the other regions. We also found the lowest projected future coral cover in the Caribbean. These findings suggest that coral reef persistence depends on ecology, evolution, and habitat network characteristics, and that, under an emissions stabilization scenario (RCP 4.5), recovery may be possible over multiple centuries.

Evolution reverses the effect of network structure on metapopulation persistence - Lisa C. McManus; Eden Tekwa; Daniel E. Schindler; Timothy E. Walsworth; Madhavi A. Colton; Michael M. Webster; Timothy E. Essington; Daniel L. Forrest; Stephen R. Palumbi; Peter J. Mumby; Malin L. Pinsky (Ecology, 2021)
Global environmental change is challenging species with novel conditions, such that demographic and evolutionary trajectories of populations are often shaped by the exchange of organisms and alleles across landscapes. Current ecological theory predicts that random networks with dispersal shortcuts connecting distant sites can promote persistence when there is no capacity for evolution. Here, we show with an eco‐evolutionary model that dispersal shortcuts across environmental gradients instead hinder persistence for populations that can evolve because long‐distance migrants bring extreme trait values that are often maladaptive, short‐circuiting the adaptive response of populations to directional change. Our results demonstrate that incorporating evolution and environmental heterogeneity fundamentally alters theoretical predictions regarding persistence in ecological networks.

The effects of normoxic endurance exercise on erythropoietin (EPO) production and the impact of selective β1 and non-selective β1 + β2 adrenergic receptor blockade - Rod J. Azadan; Nadia H. Agha; Hawley E. Kunz; Forrest L. Baker; Preteesh L. Mylabathula; Tracy A. Ledoux; Daniel P. O’Connor; Charles R. Pedlar; Richard J. Simpson (European Journal of Applied Physiology, 2021)

Beyond ecosystem modeling: A roadmap to community cyberinfrastructure for ecological data‐model integration - Istem Fer; Anthony K. Gardella; Alexey N. Shiklomanov; Eleanor E. Campbell; Elizabeth M. Cowdery; Martin G. De Kauwe; Ankur Desai; Matthew J. Duveneck; Joshua B. Fisher; Katherine D. Haynes; Forrest M. Hoffman; Miriam R. Johnston; et al. (Global Change Biology, 2021)
In an era of rapid global change, our ability to understand and predict Earth's natural systems is lagging behind our ability to monitor and measure changes in the biosphere. Bottlenecks to informing models with observations have reduced our capacity to fully exploit the growing volume and variety of available data. Here, we take a critical look at the information infrastructure that connects ecosystem modeling and measurement efforts, and propose a roadmap to community cyberinfrastructure development that can reduce the divisions between empirical research and modeling and accelerate the pace of discovery. A new era of data‐model integration requires investment in accessible, scalable, and transparent tools that integrate the expertise of the whole community, including both modelers and empiricists. This roadmap focuses on five key opportunities for community tools: the underlying foundations of community cyberinfrastructure; data ingest; calibration of models to data; model‐data benchmarking; and data assimilation and ecological forecasting. This community‐driven approach is a key to meeting the pressing needs of science and society in the 21st century.

Wildlife impacts and vulnerable livelihoods in a transfrontier conservation landscape - Jonathan Salerno; Karen Bailey; Andrea E. Gaughan; Forrest R. Stevens; Tom Hilton; Lin Cassidy; Michael D. Drake; Narcisa G. Pricope; Joel Hartter (Conservation Biology, 2020)
Interactions between humans and wildlife resulting in negative impacts are among the most pressing conservation challenges globally. In regions of smallholder livestock and crop production, interactions with wildlife can compromise human well‐being and motivate negative sentiment and retaliation toward wildlife, undermining conservation goals. Although impacts may be unavoidable when human and wildlife land use overlap, scant large‐scale human data exist quantifying the direct costs of wildlife to livelihoods. In a landscape of global importance for wildlife conservation in southern Africa, we quantified costs for people living with wildlife through a fundamental measure of human well‐being, food security, and we tested whether existing livelihood strategies buffer certain households against crop depredation by wildlife, predominantly elephants. To do this, we estimated Bayesian multilevel statistical models based on multicounty household data ( n = 711) and interpreted model results in the context of spatial data from participatory land‐use mapping. Reported crop depredation by wildlife was widespread. Over half of the sample households were affected and household food security was reduced significantly (odds ratio 0.37 [0.22, 0.63]). The most food insecure households relied on gathered food sources and welfare programs. In the event of crop depredation by wildlife, these 2 livelihood sources buffered or reduced harmful effects of depredation. The presence of buffering strategies suggests a targeted compensation strategy could benefit the region's most vulnerable people. Such strategies should be combined with dynamic and spatially explicit land‐use planning that may reduce the frequency of negative human–wildlife impacts. Quantifying and mitigating the human costs from wildlife are necessary steps in working toward human–wildlife coexistence.

The interim management procedure approach for assessed stocks: Responsive management advice and lower assessment frequency - Quang C. Huynh; Adrian R. Hordyk; Robyn E. Forrest; Clay E. Porch; Sean C. Anderson; Thomas R. Carruthers (Fish and Fisheries, 2020)
Stock assessments are often used to provide management advice, such as a total allowable catch (TAC), to fishery managers. Many stocks are not assessed annually, and the TAC from the previous assessment is often maintained in years between assessments. We developed two interim management procedures (MPs) that update the estimate of current vulnerable biomass from a surveyed index of abundance to adjust the TAC from a previous assessment. These MPs differ in how they handle uncertainty in observed indices. Using closed‐loop simulation, we evaluated the two interim MPs (with 10‐ and 5‐year assessment intervals) against several “status quo” approaches: (1) an annual assessment, and (2) a stock assessment every 5 or 10 years with (a) fixed TACs or (b) projections between assessments. We evaluated performance across three life‐history types and six operating model scenarios. The interim MPs performed similarly to annual assessments in terms of trends in biomass and yield, regardless of the assessment interval of the interim MPs. The interim MPs often produced more yield than the Fixed TAC MP with 10‐year assessment intervals, for example, in depleted scenarios. The Fixed TAC MP performed more similarly to interim MPs when the assessment interval for the Fixed TAC MP was decreased to five years. The interim MPs can also perform well when circumstances arise that are not accounted for in the Projection MP. Our results show that interim MPs should be considered for infrequently assessed stocks or rebuilding stocks, and highlight potential cost savings of interim MPs over annual assessments.

Pyramidal cell-selective GluN1 knockout causes impairments in salience attribution and related EEG activity - Alexandra D. Forrest; Jakyung Bang; Robert E. Featherstone; Jonathan H. Bloom; Matthew S. Luminais; Rebecca V. Zhang; Christopher R. Gajewski; Mary F. McMullen; Yuling Liang; Steven J. Siegel (Experimental Brain Research, 2018)

Wildfire, climate, and perceptions in Northeast Oregon - Lawrence C. Hamilton; Joel Hartter; Barry D. Keim; Angela E. Boag; Michael W. Palace; Forrest R. Stevens; Mark J. Ducey (Regional Environmental Change, 2016)

Hydro-economic analysis of groundwater pumping for irrigated agriculture in California’s Central Valley, USA - Josué Medellín-Azuara; Duncan MacEwan; Richard E. Howitt; George Koruakos; Emin C. Dogrul; Charles F. Brush; Tariq N. Kadir; Thomas Harter; Forrest Melton; Jay R. Lund (Hydrogeology Journal, 2015)

Linking vegetation response to seasonal precipitation in the Okavango–Kwando–Zambezi catchment of southern Africa - Andrea E. Gaughan; Forrest R. Stevens; Cerian Gibbes; Jane Southworth; Michael W. Binford (International Journal of Remote Sensing, 2012)

Effects of climate‐driven primary production change on marine food webs: implications for fisheries and conservation - C. J. BROWN; E. A. FULTON; A. J. HOBDAY; R. J. MATEAR; H. P. POSSINGHAM; C. BULMAN; V. CHRISTENSEN; R. E. FORREST; P. C. GEHRKE; N. A. GRIBBLE; S. P. GRIFFITHS; H. LOZANO‐MONTES; et al. (Global Change Biology, 2010)
Climate change is altering the rate and distribution of primary production in the world's oceans. Primary production is critical to maintaining biodiversity and supporting fishery catches, but predicting the response of populations to primary production change is complicated by predation and competition interactions. We simulated the effects of change in primary production on diverse marine ecosystems across a wide latitudinal range in Australia using the marine food web model Ecosim. We link models of primary production of lower trophic levels (phytoplankton and benthic producers) under climate change with Ecosim to predict changes in fishery catch, fishery value, biomass of animals of conservation interest, and indicators of community composition. Under a plausible climate change scenario, primary production will increase around Australia and generally this benefits fisheries catch and value and leads to increased biomass of threatened marine animals such as turtles and sharks. However, community composition is not strongly affected. Sensitivity analyses indicate overall positive linear responses of functional groups to primary production change. Responses are robust to the ecosystem type and the complexity of the model used. However, model formulations with more complex predation and competition interactions can reverse the expected responses for some species, resulting in catch declines for some fished species and localized declines of turtle and marine mammal populations under primary productivity increases. We conclude that climate‐driven primary production change needs to be considered by marine ecosystem managers and more specifically, that production increases can simultaneously benefit fisheries and conservation. Greater focus on incorporating predation and competition interactions into models will significantly improve the ability to identify species and industries most at risk from climate change.

Phosphorus uptake by Typha leaf litter as affected by oxygen availability - Kevin A. Grace; Forrest E. Dierberg; Thomas A. DeBusk; John R. White (Wetlands, 2008)

The effects of calling song spacing and intensity on the attraction of flying crickets (orthoptera: Goryllidae: Nemobiinae) - H. E. Farris; T. G. Forrest; R. R. Hoy (Journal of Insect Behavior, 1997)

Interaction between nickel and iron in the rat - Forrest H. Nielsen; Terrence R. Shuler; Thomas J. Zimmerman; Michael E. Collings; Eric O. Uthus (Biological Trace Element Research, 1979)